2011
DOI: 10.1002/pbc.24037
|View full text |Cite
|
Sign up to set email alerts
|

Influence of severity of anemia on clinical findings in infants with sickle cell anemia: Analyses from the BABY HUG study

Abstract: Background Clinical complications of sickle cell anemia begin in infancy. BABY HUG (ClinicalTrials.gov, NCT00006400) was a NHLBI-NICHD supported randomized phase III placebo-controlled trial of hydroxyurea (HU) in infants (recruited at 9–18 months) unselected for clinical severity with sickle cell anemia. This secondary analysis of data from BABY HUG examines the influence of anemia on the incidence of sickle cell related complications, and the impact of hydroxyurea therapy in altering these events by comparin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 22 publications
2
30
0
1
Order By: Relevance
“…The impact of hydroxyurea on TCD velocity was previously reported; at baseline, TCD velocity was negatively correlated with hemoglobin level. 8,9 The average increase in TCD velocity during the study was significantly lower in the hydroxyurea group. 1,8,9 Gallbladder disease.…”
Section: Sickle Cell-related Clinical Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of hydroxyurea on TCD velocity was previously reported; at baseline, TCD velocity was negatively correlated with hemoglobin level. 8,9 The average increase in TCD velocity during the study was significantly lower in the hydroxyurea group. 1,8,9 Gallbladder disease.…”
Section: Sickle Cell-related Clinical Eventsmentioning
confidence: 99%
“…8,9 The average increase in TCD velocity during the study was significantly lower in the hydroxyurea group. 1,8,9 Gallbladder disease. On abdominal ultrasound at study exit, 8 children in the hydroxyurea group and 6 children in the placebo group had sludge and 5 children in the hydroxyurea group and 5 children in the placebo group had cholelithiasis.…”
Section: Sickle Cell-related Clinical Eventsmentioning
confidence: 99%
“…11 We assessed risk factors for developing MiA, tested the hypothesis that early severe anemia is a risk factor for developing MiA, and analyzed our cohort based on the KDIGO definition of CKD. 14 We conducted an institutional review board-approved pediatric SCD nephropathy prospective cohort of 152 patients (.5 years) with hemoglobin SS (HbSS) or HbSB 0 thalassemia. We recorded every spot urine albumin/creatinine level obtained since birth (n 5 595) and prospectively collected annual urine measurements along with clinical and laboratory values.…”
mentioning
confidence: 99%
“…15 "Early severe anemia" was categorized as Hb ,8.0 g/dL on their earliest complete blood count (CBC) between 12 and 24 months of age. 14 We analyzed age, sex, blood pressure, laboratory variables, and current therapy from the visit that coincided with identification of MiA and an early CBC to identify associations with MiA using t tests and x 2 tests for continuous and categorical variables, respectively. To examine the time to development of MiA and its predictors, we used Weibull parametric survival regression model, which accommodates left, right, and interval censored data.…”
mentioning
confidence: 99%
“…Last year witnessed the culmination of a decade-long Phase III clinical trial (BABY HUG) involving infants with SCA randomized either to HU (fixed dose 20 mg/kg/day) or placebo. BABY HUG showed that HU did not clearly prevent organ damage in a 2-year treatment period, but significantly decreased pain, ACS, hospitalizations, and transfusions in children [25][26][27][28][29][30].…”
Section: Existing Treatmentmentioning
confidence: 99%